Security Home Door Automation Using Multi Sensors - Kristi Mahardi; Joni Welman Simatupang; Evi Rismauli (President University, 2021)
The System is using Smart Relay as main control that is commonly used industrially and commercially as a control system. Using the smart relay can reduce the use of control relay and writing of the system significantly. The smart relay has a GSM-SMS for messaging and controlling the system. Only the listed number at the system that can message and control the system. By using smart relay, we can costumized our design as our requirements. Automatic door is commonly used in commercial and industrial. The relay output will be connected to door motor (for opening and closing), buzzer for alarm and pilot lamps for indication. Finaly the system is expected to have several functions as follow : Automatic opening door using fingerprint detection, automatic opening door using GSM command, automatic opening door using push button for inside command, automatic opening door using passcode, automatic closing door after door is fully opened with no movement and send the notification by GSM. By Implementing this system, it will be easier to lock the door and activate the alarm from a considerable distance.